Politics of Food. : Edited by Aaron Cezar, Dani Burrows. - Cezar, Aaron; Adrià, Ferran; Arzak, Marta; Böhm, Kathrin; Contini, Leone; Taussig, Michael; Lang, Tim; Holden, Patrick; Sansour, Vivian
Cooking Sections ; Gill, MacDonald ; Laessing, Nick ; Okudzeto, Senam ; Yassin, Raed ; Salomon, Daniel ; Makhacheva, Taus
Voeding, ethiek, antropologie, activisme, klimaat, ecologie, gezondheid, identiteit
boek